Un’etnografia del gioco d’azzardo: La ricerca antropologica e la pianificazione di progetti di prevenzione sulle dipendenze patologiche - Lenzi Grillini, Filippo (Antropologia Pubblica, 2024)
This paper aims to analyze an anthropological consultancy assignment conducted within a project focused on addictions. In this specific case the purpose of the article is to shed the light on the main problems and the opportunities offered by an ethnoanthropological research commissioned by a non-academic entity. The paper builds on the work of the “Pathological Addiction Operative Unit” of Siena Local Health Authority, which employed an anthropological consultant to research pathological gambling. In this context the anthropologist has to interact with professionals with different disciplinary backgrounds, mainly biomedical practitioners. These, for the first time in their professional life, deal with an anthropologist who uses a very different research methodology and theoretical basis. More specifically this paper focuses on the time-consuming nature of the ethnographic research with respect to the needs of results required by the “Pathological Addiction Operative Unit”. Furthermore, the possible negotiation strategies with the client are discussed. Finally, this article presents general considerations on the potential role and opportunities for anthropological research in the biomedical field, nowadays in Italy.